Turning a lost reef ecosystem into a national restoration program - Dominic McAfee; Ian M. McLeod; Heidi K. Alleway; Melanie J. Bishop; Simon Branigan; Sean D. Connell; Craig Copeland; Christine M. Crawford; Ben K. Diggles; James A. Fitzsimons; Ben L. Gilby; Paul Hamer; et al. (Conservation Biology, 2022)
Achieving a sustainable socioecological future now requires large‐scale environmental repair across legislative borders. Yet, enabling large‐scale conservation is complicated by policy‐making processes that are disconnected from socioeconomic interests, multiple sources of knowledge, and differing applications of policy. We considered how a multidisciplinary approach to marine habitat restoration generated the scientific evidence base, community support, and funding needed to begin the restoration of a forgotten, functionally extinct shellfish reef ecosystem. The key actors came together as a multidisciplinary community of researchers, conservation practitioners, recreational fisher communities, and government bodies that collaborated across sectors to rediscover Australia's lost shellfish reefs and communicate the value of its restoration. Actions undertaken to build a case for large‐scale marine restoration included synthesizing current knowledge on Australian shellfish reefs and their historical decline, using this history to tell a compelling story to spark public and political interest, integrating restoration into government policy, and rallying local support through community engagement. Clearly articulating the social, economic, and environmental business case for restoration led to state and national funding for reef restoration to meet diverse sustainability goals (e.g., enhanced biodiversity and fisheries productivity) and socioeconomic goals (e.g., job creation and recreational opportunities). A key lesson learned was the importance of aligning project goals with public and industry interests so that projects could address multiple political obligations. This process culminated in Australia's largest marine restoration initiative and shows that solutions for large‐scale ecosystem repair can rapidly occur when socially valued science acts on political opportunities.

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Unexpected removal of the most neutral cationic pharmaceutical in river waters - Alan D. Tappin; J. Paul Loughnane; Alan J. McCarthy; Mark F. Fitzsimons (Environmental Chemistry Letters, 2016)

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Removal of atrazine from river waters by indigenous microorganisms - Alan D. Tappin; J. Paul Loughnane; Alan J. McCarthy; Mark F. Fitzsimons (Environmental Chemistry Letters, 2012)